Peran Pegadaian Syariah dalam Meningkatkan Literasi Keuangan Masyarakat di Era Digital - Padly Nahampun; Muhamad syahwildan; Ade Syahrozi; Raid Fakhri Muhtaram; Nahampun Widia Pratama (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study explores the role of Islamic pawnshops (Pegadaian Syariah) in enhancing financial literacy among Indonesian communities in the context of rapid digital transformation. Using a qualitative descriptive method through literature review and contextual observation, the research analyzes how Pegadaian Syariah integrates educational initiatives with digital innovations to empower financially underserved populations. Findings indicate that Pegadaian Syariah serves not only as a financial intermediary but also as a community-based educational institution. Through mobile applications, digital campaigns, and community outreach, it actively contributes to improving public understanding of financial management from a sharia-compliant perspective. However, challenges remain, including low digital literacy and resistance to adopting digital platforms. Despite this, the institution holds significant potential to become a catalyst for inclusive financial education and sustainable economic behavior, particularly in low-to-middle-income segments. The study suggests a need for collaborative efforts and context-sensitive strategies to optimize the impact of digital financial education in rural and semi-urban areas.